CHARACTERIZATION OF PLIEK U FUNGUS AND CARBOHYDRATE FERMENTATION TEST - Zuraidah, Zuraidah; Daniah, Daniah; Suryani, Suryani (Biotik, 2023)
Pliek u, also known as patarana, is a traditional coconut oil produced by the people of Aceh, especially in Dayah Bubue Village, Pidie. The fermented oil from pliek u is often used by the villagers to be applied to itchy skin or wounds. It is necessary to isolate and identify the characteristics of isolates from pliek u and test isolates against carbohydrate fermentation in order to know the potential of pliek u isolates which are often used as seasonings for Acehnese cuisine. The purpose of this study was to identify the characteristics of fungal colonies found in the process of making pliek u, examine the physical factors of the substrate on fungal growth, and examine the results of carbohydrate fermentation tests. Research procedures: sampling at the research site in Dayah Bubue Village, Pidie, the process of isolating fungi from pliek u, culture purification, identification, and carbohydrate fermentation tests. The results of the research at the initial stage of fermentation found Soradia sp. and Curvularia sp., the final stage of fermentation found Soradia sp. and Microascus sp., pliek u stage found Mucor sp. Fungal characters in general large colonies, irregular shapes, round colonies, flat elevations, and notched margins. Changes in temperature and pH greatly affect the presence of pliek u. The five fungal isolates reacted positively to glucose and sucrose fermentation, but did not react positively to the lactose test.